2004
DOI: 10.1007/s00426-004-0178-5
|View full text |Cite
|
Sign up to set email alerts
|

Total retrieval time and hypermnesia: Investigating the benefits of multiple recall tests

Abstract: Hypermnesia is an increase in recall over repeated tests. A core issue is the role of repeated testing, per se, versus total retrieval time. Prior research implies an equivalence between multiple recall tests and a single test of equal total duration, but theoretical analyses indicate otherwise. Three experiments investigated this issue using various study materials (unrelated word lists, related word lists, and a short story). In the first experimental session, the study phase was followed by a series of shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
(105 reference statements)
1
23
0
Order By: Relevance
“…The finding of a positive effect of repeated testing on memory retention is in line with several other studies (Kelley and Nairne, 2003;Mulligan, 2005). Furthermore, the results show that less forgetting occurs in the presence of intermediate free recalls, indicating that recalling the words on several occasions has a positive effect on long-term memory and leads to a more resistant memory trace.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding of a positive effect of repeated testing on memory retention is in line with several other studies (Kelley and Nairne, 2003;Mulligan, 2005). Furthermore, the results show that less forgetting occurs in the presence of intermediate free recalls, indicating that recalling the words on several occasions has a positive effect on long-term memory and leads to a more resistant memory trace.…”
Section: Discussionsupporting
confidence: 90%
“…This free recall procedure has been criticized because of the repeated testing of the same material. After all, recalling an item increases the likelihood that it will be recalled at a later time (Kelley and Nairne, 2003;Mulligan, 2005). Therefore, it could be that the observed D-amphetamine facilitation effect on verbal memory performance is not only caused by a modulation of the consolidation process, but also by processes related to retrieval.…”
Section: Introductionmentioning
confidence: 87%
“…Thus, we propose that participants in Group 1 (Amnesia-Accurate) performed worse than did participants in Group 2 (Accurate-Accurate) on the delayed free and cued recall tests because Group 1 had less practice at recalling the facts of a story correctly than did Group 2. As previous research has demonstrated, recall repetition enhances accuracy (Mulligan, 2005), This same recall practice interpretation can account for the performance of Groups 1 (Amnesia-Accurate) and 3 (No Recall-Accurate) on the delayed free recall and cued recall tests. In the present experiments, we limited the amount of information requested for free recall in order to make the amount to be recalled manageable and to focus the recall on the details surrounding the death of a character.…”
Section: Discussionmentioning
confidence: 86%
“…However, as Christianson and Bylin noted, the better recall of the accurate participants on the delayed tests than of the participants who had previously feigned amnesia could have been due to either the inhibitory consequences of previously faking amnesia or, more simply, practice at recalling the facts of the story correctly. Participants in the accurate condition had more practice recalling correctly than did participants in the feigned amnesia condition, and research on repeated recall indicates that recall repetition enhances accuracy (see, e.g., Mulligan, 2005). Bylin and Christianson (2002) addressed this issue in a follow-up study in which they added a necessary control condition.…”
Section: Does Feigning Amnesia Impair Subsequent Recall?mentioning
confidence: 99%
“…However, at least some gains can also be achieved by other factors: For example, previous retrieval attempts might have failed in spite of a sufficiently strong memory trace due to distraction, incomplete search, reduced attentional resources etc. Furthermore, simply repeating retrieval attempts without any retention interval leads to increases in recall success and can produce memory gains, a phenomenon known as "hypermnesia" (Mulligan, 2005;Roediger & Payne, 1982). And finally, if we assume that retrieval is a probability process depending on the strength of the memory trace, some gains will always occur by chance.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%